Molecular chaperones: assisting assembly in addition to folding. - Ellis (Trends in Biochemical Sciences, 2006)
The common perception that molecular chaperones are involved primarily with assisting the folding of newly synthesized and stress-denatured polypeptide chains ignores the fact that this term was invented to describe the function of a protein that assists the assembly of folded subunits into oligomeric structures and only later was extended to embrace protein folding. Recent work has clarified the role of nuclear chaperones in the assembly of nucleosomes and has identified a cytosolic chaperone required for mammalian proteasome assembly, suggesting that the formation of other oligomeric complexes might be assisted by chaperones.